SETENGAH ABAD AMALGAMASI ANTARA ETNIS JAWA DENGAN ETNIS TEMPATAN DI DESA SIABU KECAMATAN SALO KABUPATEN KAMPAR - Kardiyan "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research conducted in the village of Salo Siabu District of Kampar which aims to determine what factors affect Siabu village communities to undertake different wedding cultures or amalgamation. This study, entitled "Half a Century Amalgamation Between Ethnic Javanese With Locale In the village Siabu Salo District of Kampar". Formulation of the problem in this research was to determine the characteristics of the people who do the amalgamation, to know what factors affect people do amalgamation. To determine the assimilation and acculturation that occured in couples who do amalgamation. The skind of the research used in this research was descriptive qualitative research. Data collection was done by interview, observation and documentation. The tools used were interview guidelines. Mechanical for collecting respondents in this study was purposive sampling of respondents withdrawal based on certain criteria. The results showed that the Javanese ethnic communities and local ethnic already well integrated with the achievement of different cultures in society wedding. Factors affecting villagers in Siabu do amalgamation was the similarity of religion, equality of work or socio-economic status as well as the similarity of residence. Assimilation and acculturation that occured in pairs amalgamsi covers in terms of language. Acculturation and assimilation which occured in pairs amlagamasi the village community Siabu influenced by the dominance of a couple of her partner and was also influenced by the neighborhood. Keywords: Amalgamation, Factors Affecting Amalgamation